Seleksi Anggota Paduan Suara Menggunakan Metode Fuzzy Tsukamoto dan Simple Additive Weighting (SAW) - Genjah Amartha Gora; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The choir is a term refers to a music ensemble consisting of singers and music collaborated into a single ensemble. The Jeuvana vocalista was first established in 1990 with three members. Many people all the time interest in the choir, the achievements earned in the choir every year . Jeuvana vocalista studio is increasingly more interested from year, then they make the selection for those interested in being a member of a particular choir team, because one of the more importance the quality of each person to be able to join a team of choir. At the moment there is no application used to assist the selection of Studio Jeuvana vocalista in choosing members of the Choir. The solving problems that exist in jeuvana vocalista studio, applied to choosing choir members using Fuzzy Tsukamoto and Simple Additive Weighted method. The Fuzzy Tsukamoto method to help simplify the selection. The output is a recommended exercise that should be followed by three months. Simple Additive Weighting to determine the rank of dedicated singers in the field of drag votes. Testing Correlation program in each year 2015, 2016, 2017 of 0.98, 0.94 and 0.87. From the results of the program and coach decisions are in line and have a positive and equally strong correlation value.